Decellularization of aorta tissue using sonication treatment as potential scaffold for vascular tissue engineering - Nurul , Syazwani; Noor Azmi, Azran Azhim; Yuji, Morimoto; Takashi , Ushida; Katsuko , Furukawa (Springer Berlin Heidelberg, 2015)
Arterial scaffolds have potential for replacing native arteries for vascular surgery. These scaffolds are anti-thrombogenic, biocompatible, and capable of growth and repair, making them suitable for application in vascular tissue engineering. This study develops a sonication decellularization system for preparing a complete decellularized artery. The sonication decellularization efficiency on arterial tissues is investigated. Aorta samples are decellularized by sonication treatment with various treatment times and application of sodium dodecyl sulfate (SDS) detergent with and without saline. The relation between decellularization and dissolved oxygen concentration is investigated. The treated samples are evaluated using hematoxylin–eosin staining, scanning electron microscopy, diamidino-2-phenylindol (DAPI) staining, biomechanical testing, and DNA quantification. From the histological analysis, sonication treatment without saline shows complete decellularization at a specific region on the extracellular matrix. This is further confirmed by the DAPI staining, which demonstrates complete removal of DNA fragments for sonication treatment in 2 % SDS without saline. Sonication treatment without saline is thus capable of producing complete decellularized scaffolds for vascular tissue engineering.